2014
DOI: 10.15344/2349-2635/2014/103
|View full text |Cite
|
Sign up to set email alerts
|

Non-conscious Effects of Marketing Communication and Implicit Attitude Change: State of Research and New Perspectives

Abstract: The article shows that many psychological effects of the marketing communication, sometimes called "non-conscious effects", really produce implicit attitude changes. We show that the theoretical and methodological framework of implicit attitude is well adapted to study these effects and to open new perspectives to study the persuasion in a marketing communication context. On the basis of research conducted within advertising contexts, product placement and TV sponsorship, four types of non-conscious influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 98 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Gawronsk and Houwer (2014) stress the need for implicit measures over explicit measures such as self-reporting; hence, neuroscience techniques in marketing research Emotional and cognitive responses provide deeper insights into unconscious thoughts and behaviour. Further, Courbet and Fourquet-Courbet (2014) found that there has been significant progress in research in social and cognitive psychology that uses implicit measures; this proves that an important part of the psychological activity involved in thinking, judgements, feelings and behaviours is unconscious. This study is innovative the tourism field, in that it uses neuroscience techniques to better understand the processes of the non-conscious influence of marketing communications and their memory, attitudinal and behavioural effects.…”
Section: Destination Image Research and Non-conscious Research On Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gawronsk and Houwer (2014) stress the need for implicit measures over explicit measures such as self-reporting; hence, neuroscience techniques in marketing research Emotional and cognitive responses provide deeper insights into unconscious thoughts and behaviour. Further, Courbet and Fourquet-Courbet (2014) found that there has been significant progress in research in social and cognitive psychology that uses implicit measures; this proves that an important part of the psychological activity involved in thinking, judgements, feelings and behaviours is unconscious. This study is innovative the tourism field, in that it uses neuroscience techniques to better understand the processes of the non-conscious influence of marketing communications and their memory, attitudinal and behavioural effects.…”
Section: Destination Image Research and Non-conscious Research On Imagesmentioning
confidence: 99%
“…The reasons that have been attributed for this rise in research dealing with psychological processing methods, include a growing number of communication media, in particular, internet sites and television channels (with the immense growth of cable television), for example, web banners, television sponsorship and product placement in movies, which make low-attention quickly forgotten exposures more frequent (Courbet and Fourquet-Courbet, 2014). For example, Kim et al (2014), used psychophysiological measures to determine how individuals process two types of advertising communications video and high-imagery audio advertisements concerning mental imagery processing.…”
Section: Destination Image Research and Non-conscious Research On Imagesmentioning
confidence: 99%
“…The need for technology to counter pervasive advertising is more urgent because of increased interest in nonconscious advertising [17], in line with interest in nonconscious techniques in health and behaviour change [53,57]. Acar notes that advertisers are exploring "incidental advertising processing, states of unconscious learning, and preattentive exposure effects" [1].…”
Section: Nonconscious Advertisingmentioning
confidence: 99%
“…Creators, users, and regulators of signage could benefit from an understanding of how a given sign may be processed quite differently (or not at all) by different members of an audience as a function of motivational states. As an example of an implication for design, signs should be constructed to represent brands/organizations and convey messages though multiple routes, including both conscious and automatic, unconscious processes (Courbet & Fourquet-Courbet, 2014), because communication takes places via different routes for individuals characterized by different motivational states or traits. As an example of a regulatory implication, consider that in some cases signage may be like a warning label on a bottle of medicine.…”
Section: Person Traitsmentioning
confidence: 99%
“…Unconscious processes, by contrast, are generally less well known and less understood (Courbet & Fourquet-Courbet, 2014). Yet they may offer better explanations for how signage works.…”
Section: Processesmentioning
confidence: 99%